2008
DOI: 10.1002/ddrr.9
|View full text |Cite
|
Sign up to set email alerts
|

Genes, brain development and psychiatric phenotypes in velo‐cardio‐facial syndrome

Abstract: Velo-cardio-facial syndrome (VCFS) has been in the focus of intensive research over the last 15 years. The syndrome represents a homogeneous model for studying the effect of a decreased dosage of genes on the development of brain structure and function and, consequently, on the emergence of schizophrenia-like psychotic disorder. In this review, we describe the psychiatric phenotype of children, adolescents, and young adults with VCFS. We redefine the concept of "behavioral phenotype" and suggest that psychosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
96
3
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 109 publications
6
96
3
2
Order By: Relevance
“…Consistently, parietal lobe gray matter volumes are often found to be reduced in children with 22q11DS (Eliez et al, 2000;Kates et al, 2001), and a recent report suggests that gyrification in the precuneus/PCC regions is more affected in children with 22q11DS as a result of congenital heart defects associated with this deletion syndrome (Schaer et al, 2009b). Observing parietal resting-state functional dysconnectivity for the first time provides the missing link between previously reported structural alterations of parietal gray and white matter (Gothelf et al, 2008) and visuo-spatial/ arithmetic impairments in 22q11DS (Bearden et al, 2001;De Smedt et al, 2007b;Simon et al, 2008). Most probably, this altered cerebral development is sustained by cerebral structure dysmaturation, functional dysconnectivity and their interactions with developing skills in the visuo-spatial domain (Simon et al, 2005(Simon et al, , 2008.…”
Section: Discussionmentioning
confidence: 57%
“…Consistently, parietal lobe gray matter volumes are often found to be reduced in children with 22q11DS (Eliez et al, 2000;Kates et al, 2001), and a recent report suggests that gyrification in the precuneus/PCC regions is more affected in children with 22q11DS as a result of congenital heart defects associated with this deletion syndrome (Schaer et al, 2009b). Observing parietal resting-state functional dysconnectivity for the first time provides the missing link between previously reported structural alterations of parietal gray and white matter (Gothelf et al, 2008) and visuo-spatial/ arithmetic impairments in 22q11DS (Bearden et al, 2001;De Smedt et al, 2007b;Simon et al, 2008). Most probably, this altered cerebral development is sustained by cerebral structure dysmaturation, functional dysconnectivity and their interactions with developing skills in the visuo-spatial domain (Simon et al, 2005(Simon et al, , 2008.…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, function does not only reflect underlying structural alterations but can also be the result of an adaptation to a different structural background. Such complex relationships could explain why we observe only few discriminative connections in the functional network of the parietal lobe whereas structural alterations are consistently reported in this region (Antshel et al 2008b;Gothelf et al 2008). Investigation of brain connectivity with multimodal neuroimaging approaches, task-related fMRI or dynamic measurements of connectivity will be necessary to provide new a b Fig.…”
Section: Discriminating Patients With 22q11ds From Healthy Controlsmentioning
confidence: 91%
“…Introduction 22q11.2 deletion syndrome (22q11DS) is a neurogenetic condition which draws particular interest as a model to understand the pathogenesis of schizophrenia . A variety of genes have been identified in the 3Mb deletion associated with 22q11DS, among which haploinsufficiency of the catechol-O-methyltransferase (COMT) gene has received a large emphasis (Gothelf et al, 2008). From the point of view of structural neuroimaging, a large body of literature is aimed at delineating the cerebral phenotype in these individuals at risk for developing schizophrenia.…”
mentioning
confidence: 99%
“…From the point of view of structural neuroimaging, a large body of literature is aimed at delineating the cerebral phenotype in these individuals at risk for developing schizophrenia. Numerous studies have reported specific patterns of volumetric alterations in children and adults with the syndrome (Schaer and Eliez, 2007;Gothelf et al, 2008). However, between-group comparisons in sample with restrained age ranges only provide snapshots over the dynamic unfolding of structural brain changes with age.…”
mentioning
confidence: 99%